2023
DOI: 10.1186/s12882-023-03214-1
|View full text |Cite
|
Sign up to set email alerts
|

Elevated angiopoietin-like protein 3 serum levels in diabetic nephropathy patients and its association with renal function and lipid profile

Abstract: Background Type 2 diabetes mellitus (T2DM) is a highly prevalent disease that has life-threatening consequences like micro and macrovascular complication. Diabetic nephropathy (DN) is one of the common consequences of T2DM which is related to secretory factors like hepatokines. Angiopoietin-Like Protein 3 (ANGPTL3) is a hepatokine that is perturbated in cardiometabolic diseases and experimental studies showed its effect on renal functions and lipid metabolism. For the first time, ANGPTL3 was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Its coiled-coil domain (CCD) plays a pivotal role in lipid metabolism regulation, while the fibrinogen-like domain (FLD) is instrumental in angiogenesis, primarily through interaction with the integrin αvβ3 receptor [ 5 ]. ANGPTL3's involvement in various renal pathologies, including diabetic nephropathy [ 6 ], renal cell carcinoma [ 7 ] and acute kidney injury [ 8 ] has been documented. From a bioinformatics perspective, Yang et al [ 9 ] identified ANGPTL3 as a crucial diagnostic gene connected to immune and renal disease-related pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Its coiled-coil domain (CCD) plays a pivotal role in lipid metabolism regulation, while the fibrinogen-like domain (FLD) is instrumental in angiogenesis, primarily through interaction with the integrin αvβ3 receptor [ 5 ]. ANGPTL3's involvement in various renal pathologies, including diabetic nephropathy [ 6 ], renal cell carcinoma [ 7 ] and acute kidney injury [ 8 ] has been documented. From a bioinformatics perspective, Yang et al [ 9 ] identified ANGPTL3 as a crucial diagnostic gene connected to immune and renal disease-related pathways.…”
Section: Introductionmentioning
confidence: 99%